Relevansi, Efektivitas, dan Pengaruh Sastra Anak dalam Perkembangan Anak di Indonesia - Eny Junyanti; Nazla Maharani Umaya (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research examines the aspects of relevance, effectiveness, and impact of children's literature on the development of children in Indonesia. In the ever-evolving digital era, this study investigates how traditional children's literature continues to maintain its significance for contemporary generations. The methodology used includes a comprehensive analysis of existing literature, interviews with education experts, and observations of children's literature consumption patterns. The main findings indicate that classic children's literature maintains its relevance through the transmission of universal values and cultural heritage, as well as through adaptation into contemporary formats. The effectiveness of children's literature is proven in the improvement of literacy skills, emotional development, and social learning. Recent developments in children's literature show innovative trends, including theme diversification and the use of digital platforms. Furthermore, this research reveals the significant influence of children's literature on various aspects of development, including cognitive, emotional, social, and the formation of cultural identity. Children's literature serves as a catalyst in stimulating imagination, enriching vocabulary, and facilitating understanding of emotional complexities and social dynamics.The implications of this study emphasize the importance of integrating diverse children's literature into the education curriculum, as well as collaboration between educators, writers, and other stakeholders to create relevant and impactful content. Recommendations for future research include a deeper exploration of the long-term effects of children's literature exposure on individual development, as well as an investigation into the potential of children's literature in addressing contemporary issues such as digital literacy and global awareness.